МЕКТЕПКЕ ШЕКЕМГИ ТӘЛИМДЕ ОЙЫН ТЕХНОЛОГИЯЛАРЫНАН ПАЙДАЛАНЫЎ - Алеуова, Р.Ш. (FAN va JAMIYAT, 2018)
The article is devoted to the importance of developing games in preschool education and their place in the education and upbringing of children. It is given the analysis to the game, the main activity of preschool children and formation of children as a person through a game. Great attention is paid to the game technology at the lesson.